IMF Survey, Volume 31, Issue 14. (IMF Survey; IMF Survey, 2002)
To assist Argentina in its efforts to tackle an extremely difficult economic crisis and develop an effective recovery program, IMF Managing Director Horst Kohler announced the appointment of a panel of distinguished monetary policy advisors and IMF Executive Board approval of the country's request for an extension of a repayment to the IMF due later this month.